Optimization of production and marketing of stamped batik based on local wisdom through digital marketing - Inggit Marodiyah; Cindy Taurusta; Rizky Eka Febriansah; Aulia Putri Ramdhani; Aidah Fidayati; Ryan Ardiansyah; Muhammad Thariq Jabal Nurdin (Community Empowerment, 2024)
The development of stamped batik based on local wisdom is a strategic effort to preserve culture and enhance the competitiveness of Indonesia’s batik industry. The partners in this program faced two main challenges: limited tools and materials for production and restricted marketing reach. This community service program aims to improve the efficiency of stamped batik production by providing the necessary equipment, such as batik stamp tools, while enhancing marketing efforts through digital marketing training. The implementation methods included the procurement of production tools, socialization, and training on stamped batik techniques, as well as mentoring to ensure high-quality production outcomes. On the marketing aspect, the program provided training on product photography and videography, registration on digital platforms such as Google Maps, Google Business, Instagram, and Shopee, as well as training on e-commerce utilization. The program results demonstrated increased production capacity with the addition of tools and materials, and expanded marketing reach through partner registration on various digital platforms. This program not only supports the sustainability of stamped batik culture based on local wisdom but also strengthens the competitiveness of the partners in a broader market.